Hipermídia TermoQuim : uma estratégia pedagógica para o ensino de Química - Cardoso, Mônica Santana (2013)
The hypermedia tend to function as a tool that assists the teacher in the teaching-learning process, it presents several possibilities for the individual to build concepts, interacting with simulations, animations, accessing texts, videos, pictures, sounds and links that will contribute to their learning. By making use of different forms of language, hypermedia allow the use of different methodologies and assists the teacher to meet the differences of each student. Diagnosed in previous studies, there are already some hypermedia facing the teaching of chemistry, however, was not found on teaching Thermochemistry. Considering that in a survey of chemistry teachers in public schools to Thermochemistry of Mato Grosso was cited as one of the most difficult content to work in high school. Thus, this study shows how the theme of Information and Communication Technologies in Education, being the object of his search an educational product, a hypermedia. We investigated the contribution of hypermedia TermoQuim on Thermochemistry in teaching chemistry to high school students, developed during this research by analyzing the participants Institutional Scholarship Program Initiation to Teaching (Pibid) subproject of Chemistry UFMT campus Cuiabá (Proclamation 2011). The survey was conducted using a survey methodology die qualitative characteristics of case study and documentary research, and that this is an exploratory research, it has as its object of study, a hypermedia, subject still little known and exploited in teaching Chemistry. The data collection instruments used were two questionnaires, one directed study, analysis of textbooks and scientific literature review. The Hypermedia TermoQuim the following components: Presentation, Trivia, Heat and Temperature, endothermic and exothermic reactions, Calorimeter, Enthalpy, Activities, Credit and tutoring. This work allowed us to conclude that the use of hypermedia in the Teaching of Chemistry contributes positively in the teaching-learning process, because it can provide students access to different media, and allow them to act actively in the process. Thus, the proposed educational product showed himself able to assist teachers in teaching Chemistry Thermochemistry and can be used in high school and also with undergraduate students in chemistry to address the production of teaching materials. The survey results show further that the use of hypermedia can contribute effectively to the teaching of Chemistry, since this tool allows teachers to make use of various resources (video, text, sound, image, animation, simulation, experiments) to address the same content, which may oportunizar meaningful learning.